La gestión de la calidad institucional en la Universidad Nacional, Costa Rica - Ronald Miranda-Chavarría (Universidad Nacional, Costa Rica, 2004)
Proposal on the convenience of constructing a broad, integrated concept of quality management that includes academic aspects, support services and the management itself. It is set forth based on the experience achieved at Universidad Nacional on institutional quality management from 2000 to 2004; it has been supported by Dutch cooperation programs. Adopting an approach that fits together strategic aspects with constructivist and participative processes has afforded the construction of a culture and a vision of a future of quality. Some of the improvements account for achievements such as the diversification of decision making, self evaluation for self improvement or for accreditation purposes of study programs, and the establishment of improvement teams for management services. It is also acknowledged that by adopting an institutional quality management position, a gap is created between the current management procedures and those presented in the proposed model. Closing this gap will require academic authorities to play new roles and to understand that in order to build high-quality university management, it is necessary to work with a lot of precision and professionalism.